IMPLEMENTASI TEACHING AT THE RIGHT LEVEL (TaRL) DI KELAS V SEKOLAH DASAR NEGERI 1 BALEHARJO KECAMATAN EROMOKO KABUPATEN WONOGIRI TAHUN PELAJARAN 2024/2025 - Eni Mawarti; Dwi Anggraeni Siwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Teaching at the Right Level (TaRL) approach in Mathematics learning for Grade V students on the topic of Data at SD Negeri 1 Baleharjo, Eromoko District, Wonogiri Regency, in the 2024/2025 academic year. TaRL is an approach that focuses on grouping students based on their ability levels rather than their age or grade level. This research employs a qualitative descriptive method with a case study approach. Data collection techniques include interviews, observations, and documentation, which are then analyzed using the interactive analysis model by Miles and Huberman, consisting of data collection, data reduction, data presentation, and conclusion drawing. Data validity is tested through triangulation of techniques and sources. The results show that the implementation of TaRL successfully aligns learning with students' ability levels through diagnostic, formative, and summative assessments. Students are grouped based on the assessment results to ensure that the learning they receive is more tailored to their needs and capabilities. This process allows for improved learning outcomes, especially for those requiring more intensive support. This study contributes to a better understanding of how the TaRL approach can be applied within the Merdeka Curriculum to enhance more effective and student- centered learning.